2018
DOI: 10.1177/0198742918804803
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Language and Behavior in Students With Emotional Disturbance

Abstract: Although global associations between language and behavioral development are well established, relations among components and subgroups within these disorders remain unclear. The primary aim of this study was to explore whether language components differed by behavioral subtypes: internalizing only, externalizing only, or both. To control for confounding factors identified in prior studies related to sampling and measurement, we conducted profile analyses of receptive, expressive, pragmatic, semantic, syntacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
4
21
1
Order By: Relevance
“…At the same time, we should be aware of the possible underlying linguistic vulnerabilities of children with externalizing problems. Because emotional competence may mediate the relations between communication problems and externalizing problems, there may be a group of children where the emotional and behavioral problems are recognized, but language problems go unnoticed [ 22 , 63 , 64 ]. A recent review study reported 80% comorbidity of language problems and psychopathology in children who received help for their problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, we should be aware of the possible underlying linguistic vulnerabilities of children with externalizing problems. Because emotional competence may mediate the relations between communication problems and externalizing problems, there may be a group of children where the emotional and behavioral problems are recognized, but language problems go unnoticed [ 22 , 63 , 64 ]. A recent review study reported 80% comorbidity of language problems and psychopathology in children who received help for their problems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review study reported 80% comorbidity of language problems and psychopathology in children who received help for their problems. However, language problems were generally not tested and treated in these children [ 64 ]. Especially semantic and pragmatic problems are more difficult to recognize and might be misinterpreted as unwillingness or stubbornness, resulting in negative interaction patterns [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many teachers do not receive effective behavior management training (Flower, McKenna, & Haring, 2017; Moore et al, 2017; Oliver & Reschly, 2010), but the extent that SLPs are properly equipped to manage behavioral challenges is unclear. This is a particular point of concern, as 81% of children with behavior disorders have clinically meaningful and unidentified language deficits (Hollo, Wehby, & Oliver, 2014) and these deficits emerge across subdomains of language (Chow & Hollo, 2018; Hollo, Chow, & Wehby, 2018). Furthermore, children with language impairments demonstrate more problem behaviors concurrently (Curtis, Frey, Watson, Hampton, & Roberts, 2018), and are twice as likely to demonstrate behavior problems later on than their typically developing peers (Yew & O’Kearney, 2013).…”
mentioning
confidence: 99%
“…Given this common co-occurrence, an explicit focus on behavior management for school-based SLPs is an important area of need and further investigation is warranted. This is of particular importance, given that children with language impairments are likely to exhibit higher rates of problem behaviors than their peers (Curtis et al, 2018), and children with behavior disorders are more likely to need language intervention (Benner, Nelson, & Epstein, 2002; Chow & Wehby, 2019; Hollo et al, 2018). To date, the behavior management training of SLPs and the experiences SLPs have with challenging behavior in schools is limited (Beck & Dennis, 1997; Elksnin & Capilouto, 1994; Giddan, 1991).…”
mentioning
confidence: 99%